CBP and p300: HATs for different occasions - Kalkhoven, Eric (Biochemical pharmacology, 2004)
The transcriptional coactivators CREB binding protein (CBP) and p300 are key regulators of RNA polymerase II-mediated transcription. Genetic alterations in the genes encoding these regulatory proteins and their functional inactivation have been linked to human disease. Findings in patients, knockout mice and cell-based studies indicate that the ability of these multidomain proteins to acetylate histones and other proteins is critical for many biological processes. Furthermore, despite their high degree of homology, accumulating evidence indicates that CBP and p300 are not completely redundant but also have unique roles in vivo. Recent studies suggest that these functional differences could be due to differential association with other proteins or differences in substrate specificity between these acetyltransferases. Inactivation of the acetyltransferase function of either CBP or p300 in various experimental systems will no doubt teach us more about the specific biological roles of these proteins. Given the wide range of human diseases in which CBP and/or p300 have been implicated, understanding the mechanisms that regulate their activity in vivo could help to develop novel approaches for the development of therapeutic strategies.